Legal Norms in Shaping the Dual Role of Women Farmers in Tanjung Harapan, Lubuklinggau City - Efendi, Septian Fardanu; Widiono, Sumarto; Pasca Himawati, Ika (Journal of Law, Politic and Humanities, 2025)
This study analyzes the influence of legal norms on the dual role of single parent women in Tanjung Harapan, Lubuklinggau City. Using descriptive qualitative method, data were collected through interviews and observations. The results show that single parent women function as breadwinners and child caregivers, although they face major challenges due to social stigma and cultural norms that limit their roles. While there is a legal framework that supports women's rights, implementation is often inadequate, resulting in economic insecurity. This research recommends the need for more responsive policies, including skills training programs and access to business capital to empower women. By doing so, it is hoped that legal norms can adapt to social realities to improve women's welfare and active participation in socio-economic development in the community. The findings provide important insights for policymakers in formulating programs that support gender equality.